1991
DOI: 10.2307/2445257
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Dioecy in Buchloe dactyloides (Gramineae): Tests for Sex-Specific Vegetative Characters, Ecological Differences, and Sexual Niche-Partitioning

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Buchloe dactyloides is a perennial dioecious grass in which male and female inflorescences are so strikingly dimorphic that they were originally assigned to different genera. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…Males, however, were significantly taller than females in the field at the salt marsh and in the greenhouse. Other investigators have reported taller males in dioecious plants (Lloyd and Webb, 1977;Quinn, 1991;Quinn et al, 1994). Many investigators (e.g., Lloyd and Webb, 1977;Freeman et al, 1997, and references therein;Dawson and Geber, 1999) have suggested that increased height in males may aid in pollen dispersal in wind-pollinated species.…”
Section: Discussionmentioning
confidence: 98%
“…Males, however, were significantly taller than females in the field at the salt marsh and in the greenhouse. Other investigators have reported taller males in dioecious plants (Lloyd and Webb, 1977;Quinn, 1991;Quinn et al, 1994). Many investigators (e.g., Lloyd and Webb, 1977;Freeman et al, 1997, and references therein;Dawson and Geber, 1999) have suggested that increased height in males may aid in pollen dispersal in wind-pollinated species.…”
Section: Discussionmentioning
confidence: 98%
“…Among wind-pollinated species that have been investigated, flowers in the female inflorescence of Ateleia herbertsmithii, a dioecious legume, are more tightly clustered than in male inflorescences (Janzen, 1989). Striking inflorescence dimorphism in the grass Buchloe dactyloides may be related to wind pollination, because reproductive culms of male plants are taller and have more flowers than female inflorescences (Quinn, 1991), although selection on dispersal may also have been important in evolution of inflorescence dimorphism in B. dactyloides (Quinn, 1987). Significant sexual dimorphism of inflorescence structure in the Restionaceae (Kircher, 1986) is probably related to wind pollination.…”
Section: Sexual Dimorphism In Inflorescence Traitsmentioning
confidence: 99%
“…In sexually dimorphic species, the effectiveness of wind pollination might be increased by differences in secondary sex traits (Freeman et al, 1997;Lloyd & Webb, 1977). For example, in several abiotically pollinated species, the increased height of male relative to female plants, or production of more male than female flowers, may result in greater pollen dispersal by males (Lloyd & Webb, 1977;Lemen, 1980;Quinn, 1991;Bram & Quinn, 2000). Sexual dimorphism in secondary sex traits including flower size, nectar production, and inflorescence traits are also known (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The sex ratios of neighboring plants in stands of dioecious species can be expected to have consequences for ecological interactions such as fungal pathogen infections, because genetic variation can influence infection and sex is mostly genetically determined. Furthermore, sex-biased fungal infections are common (e.g., Alexander 1989;Quinn 1991). Currently, there is no established explanation of the mechanisms driving plant sex-biases in fungal pathogen infections.…”
Section: Introductionmentioning
confidence: 99%